2015
DOI: 10.1016/j.immuni.2015.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Activation of Two Pathogen-Sensing Pathways Required for Type I Interferon Expression and Resistance to an Acute DNA Virus Infection

Abstract: Summary Toll Like Receptor 9 (TLR9), its adapter MyD88, the downstream transcription factor interferon regulatory factor 7 (IRF7) and type I interferons (IFN-I) are all required for resistance to infection with ectromelia virus (ECTV). However, it is not known how or in which cells these effectors function to promote survival. Here, we showed that after infection with ECTV, the TLR9-MyD88-IRF7 pathway was necessary in CD11c+ cells for the expression of proinflammatory cytokines and the recruitment of inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
122
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(128 citation statements)
references
References 59 publications
4
122
1
1
Order By: Relevance
“…When we sorted by flow cytometry at 2.5 dpi from pooled dLNs (Figure 5A), we found that iMo (CD3 − , B220 − , NK1.1 − MHC II + CD11c + CD11b + ) and to a lesser extent classical DC (CD3 − , B220 − , NK1.1 − MHC II + CD11c + CD11b − ) but not total lymphocytes (stained with a cocktail of cascade blue-labeled Abs to CD3e, B220 and NK1.1) transcribed CXCL9 (Figure 5B) and also CXCL10 (data not shown). Similarly, we found that iMo (CD11c + , CD11b + ) and to a lesser degree DC (CD11c + CD11b − ) specifically stained intracellularly with CXCL9 mAb in the dLN at 2.5 dpi but not in the uLN (Figure 5C and Figure S2A) (note that we classified the cells in the CD11c + , CD11b + gate in the dLN plots as iMo, based on our previous extensive analysis of this population (Xu et al, 2015) using markers for DC and monocytic lineages as described by publications from the Immunolgical Genomic consortium (Gautier et al, 2012; Miller et al, 2012) and by morphology of sorted cells at the microscope). Given the post-infection excess of iMo over DC in the dLN, we conclude that iMo are the major producers of CXCL9 in the dLN and to a lesser extent, DC.…”
Section: Resultssupporting
confidence: 58%
See 4 more Smart Citations
“…When we sorted by flow cytometry at 2.5 dpi from pooled dLNs (Figure 5A), we found that iMo (CD3 − , B220 − , NK1.1 − MHC II + CD11c + CD11b + ) and to a lesser extent classical DC (CD3 − , B220 − , NK1.1 − MHC II + CD11c + CD11b − ) but not total lymphocytes (stained with a cocktail of cascade blue-labeled Abs to CD3e, B220 and NK1.1) transcribed CXCL9 (Figure 5B) and also CXCL10 (data not shown). Similarly, we found that iMo (CD11c + , CD11b + ) and to a lesser degree DC (CD11c + CD11b − ) specifically stained intracellularly with CXCL9 mAb in the dLN at 2.5 dpi but not in the uLN (Figure 5C and Figure S2A) (note that we classified the cells in the CD11c + , CD11b + gate in the dLN plots as iMo, based on our previous extensive analysis of this population (Xu et al, 2015) using markers for DC and monocytic lineages as described by publications from the Immunolgical Genomic consortium (Gautier et al, 2012; Miller et al, 2012) and by morphology of sorted cells at the microscope). Given the post-infection excess of iMo over DC in the dLN, we conclude that iMo are the major producers of CXCL9 in the dLN and to a lesser extent, DC.…”
Section: Resultssupporting
confidence: 58%
“…Note that in this case, where we used pooled LNs, there were significant differences in the levels of Cxcl9 expression between ndLN and dLN (presort) from Tlr9 −/− and Itgax-Cre + Tlr9 fl/fl mice. This suggest that the absence of a significant increase in CXCL9 in the dLN of Tlr9 −/− and Myd88 −/− mice by RT-qPCR in Figures 3C was likely due to insufficient statistical power for an experiment where there was intra-group variability, in which the n (=4) was small, and where inter-group differences were minor likely due to the very small number of iMo present in the dLN of these mice, which is 10-20 times lower than in WT mice (Xu et al, 2015). Together, these experiments show that iMo do not need autonomous TLR9 or MyD88 to produce CXCL9, and that the low amount of CXCL9 in the dLN of mice with global or CD11c + cell-restricted MyD88/TLR9 deficiency is due to their inability to efficiently recruit iMo into the dLN.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations